Stabilize, rebuild, prevent?: An overview of post-conflict resource management tools. Issue 1 (January 2017) - Roy, Vita
Highlights: Resource management is a crucial ingredient for stabilizing post-conflict situations and preventing renewed violence. Numerous tools of post-conflict resource management have been developed with implicit reference to resource-conflict links discussed in academia. Stabilization logics vary significantly across resource management tools and are sometimes contradicting each other. Abstract: When a state endowed with natural resources emerges from violent conflict, it faces a significantly higher risk of conflict recurrence. In such fragile situations, resource management may help alleviate the risk of falling back into conflict. A variety of resource management tools has emerged over the past decade that addresses fields of action spanning the entire value chain of the extractive industries, often with implicit reference to resource-conflict links discussed in literature on armed conflicts. This paper reviews the most prominent of these tools and explicates the ways in which individual resource management tools attempt to disrupt the links between resource production and recurring political violence. Future research must pay attention to mutually contradicting logics of stabilization of individual resource management tools and address the questions of adaptation and effectiveness to identify conditions under which tools and entire strategies of resource management contribute to stabilization, reconstruction, and prevention of resource-related violence.